Capitalism, populism and democracy: Revisiting Samuelson's reformulation of Schumpeter - Emilio Ocampo (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
In the 1970s and early 1980s Paul Samuelson reformulated the conditional prediction made by Joseph Schumpeter in Capitalism, Socialism and Democracy by replacing socialism with populism. According to Samuelson, "populist democracy" had attained its fullest development in the Southern Cone. He viewed Argentina as the paradigmatic case that proved his theo1y. Samuelson's thesis was that a strong electoral demand for equality and antipathy to business had hindered sustained economic growth. At the time, Samuelson also believed the advanced Western economies could follow the same path as Argentina. The Reagan and Thatcher revolution proved him wrong. However, the emergence of populism in Europe and the US in recent years makes his reformulation of Capitalism, Socialism and Democracy seem more plausible. The objective of this paper is to review and critique Samuelson's theory and to assess its relevance and usefulness today. Its main conclusions can be summarized as follows. First, Samuelson's theory is incomplete and therefore has limited power to explain current or past populist waves. Secondly, his analysis of the Argentine case was based on an erroneous interpretation of Argentine history. Third, despite being an outlier, Argentina's addiction to populism offers a cautionary tale.
Keywords: B20; B30; N16; O54; P48; 330; Samuelson; Schumpeter; Capitalism; Socialism; Democracy; Populist Democracy; Argentina; Chile; Uruguay